Repotenciación del equipo CNC Router modelo TS 1325 mediante un plan de mantenimiento integral para la empresa Ganetel S.A, de la ciudad de Guayaquil - Ecuador. - Álvarez Santana, Jorge Antonio (2019)
As part of its activities, the company PEOPE works with the CNC Router machine, electrical equipment used to make parts through the system of milling or drilling of materials such as acrylic or wood. As a result of these operations, three situations have been detected: dust contamination, high engine noise and considerable risk when handling sheets directly with the hands. As a principal objective the optimization and the integral maintenance of the CNC ROUTER machine model TS 1325 has been proposed, through the compilation of information and diagnostic about the operative state of the equipment, the elaboration of the improvement and preventive plan, also the estimation of referential costs and possible impacts of the active proposal. To solve the problems encountered, it is suggested that the first measure to be taken is the improvement and preventive maintenance to optimize the operation of the machine and protect the personal for risks in security and health. This work is a method in which the possibility of descriptive, explorative and practice execution exists because it focuses in a reality that details a particular situations. Observations and interviews were applied as field techniques. Finally, it is recommended to check that the workers in charge of the CNC Router are using the protection and security equipment for them and for the machine recommended by the fabricant, to achieve the accomplishment of the improvement and preventive maintenance proposed by the author of the actual document.